Job Contact Networks and the Ethnic Minorities - Harminder Battu; Paul Seaman; Yves Zenou (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
Using data from the UK Quarterly Labour Force Survey, this paper examines the job finding methods of different ethnic groups in the UK. Our empirical findings suggest that, though personal networks are a popular method of finding a job for the ethnic minorities, the foreign born and those who identify themselves as non-British, they are not necessarily the most effective either in terms of gaining employment or in terms of the level of job achieved. However, there are some important differences across ethnic groups with some groups losing out disproportionately from using personal networks.
Keywords: J15; J64; 330; Job search; networks; social capital; ethnic disadvantage